Constitutive activation of a variant of the env-mpl oncogene product by disulfide-linked homodimerization. - Courtois, G (1995)
The myeloproliferative leukemia retrovirus (MPLV) has the v-mpl cellular sequences transduced in frame with the deleted and rearranged Friend murine leukemia virus env gene. The resulting env-mpl fusion oncogene is responsible for an acute myeloproliferative disorder induced in mice by MPLV. v-mpl is a truncated form of the c-mpl gene which encodes the receptor for thrombopoietin. We investigated the contribution of the Env-Mpl extracellular domain in the constitutive activation of this truncated cytokine receptor and found that the rearrangement of the env sequences in the env-mpl fusion gene was not required for oncogenicity. A pathogenic variant, DEL3MPLV, was generated, which differs from MPLV by the deletions of 22 amino acids of the Env signal peptide, all of the mature Env sequences, and 18 N-terminal amino acids of the v-Mpl extracellular domain. The resulting del3-mpl oncogene product conserves in its extracellular region the first 12 amino acids of the Env signal sequence including a cysteine residue, and 25 amino acids of the v-Mpl. We show here that a mutation converting this cysteine to a glycine completely abolishes del3-mpl oncogenicity and that the del3-mpl oncogene product is constitutively activated by disulfide-linked homodimerization.